Сontent of 1,2,4-triazole derivatives in cow's milk, meat samples and animal organs after administration - Parchenko, V. V.; Panasenko, O. I.; Karpenko, Yu. V.; Kyrychko, B. P.; Zvenihorodska, T. V.; Bigdan, O. A.; Samura, T. O.; Nahorna, N. O.; Mykhailiuk, Ye. O.; Romanina, D. M.; Gutyj, B. V.; Martynyshyn, V. P.; et al. (My University, 2024)
Derivatives of 1,2,4-triazoles are widely used as active pharmaceutical ingredients (APIs) in medical preparations. The work deals with the drug “Trifuzol-neo”, the active substance of which belongs to water-soluble derivatives of 1,2,4- triazole. The aim of our work was to assess the applicability of the HPLC-MS method and determine residues of piperidinium 2-((5-(furan-2-yl)-4-phenyl-4H-1,2,4-triazol-3-yl)thio)acetate in cow milk, meat samples and animal organs after administration. The content of the medicinal substance in the cow’s milk sample was measured 24 hours after the injection of the 1% solution “Trifuzol-neo”. Active pharmaceutical ingredients concentration in the tested milk solution was 0.0695 μg/g. It was shown that 12 hours after the intramuscular injection, the active substance was not detected in the liver and spleen. 24 hours after the injection, the concentration was 0.1045 μg/g, 48 hours after the injection, the active substance was detected, but its concentration did not exceed 0.1 ppm. The developed HPLC-MS based technique is efficient and capable of being used in pharmaceutical, toxico-chemical, veterinary and food laboratories. The methodologies may be realized either in food control, or in food and veterinary investigation.
Keywords: liquid chromatography-mass spectrometry; 1,2,4-triazole; Trifuzol-neo